Decomposition and Dipteran Composition on Exposed Carcasses in an Oil Palm Plantation: A Forensic Entomology Study / Azwandi Ahmad and Abu Hassan Ahmad - Ahmad, Azwandi; Ahmad, Abu Hassan (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2008)
This is the first study on Diptera associated with carcasses carried out in north peninsular of Malaysia with reference to dry and wet climate in Malaysia. During the process of decomposition in both seasons, five phases of decay were identified namely fresh, bloated, active decay, advance decay and dry remain. In this decomposition study, biomass loss of carcass occurred rapidly from the fresh stage to the active decay stage, which was about 50% of body weight removed due to the significant colonization and feeding activity of the Diptera larvae (p < .05). Twenty-one species of adult Diptera were identified colonizing carcasses in the study period. In this study, the flies from the family of Calliphoridae, Chrysomya megacephala Fabricius (Diptera: Calliphoridae) and Chrysomya nigripes Aubertin (Diptera: Calliphoridae) were recognized as the earliest necrophagous insects arrived on the first day of exposure. Adult of Chrysomya nigripes was predominantly frequenting carcasses and abundant in the period approximately of two weeks after placement of the carcasses. By comparing the percentages of adult Diptera collected during the study period, Calliphorids abundance in wet season were 50.83%, but in dry season, the percentage of abundance was only about 35.2%. In contrast, the percentage of Sphaeroceridae family in wet season was only 3.33%, but in the dry season, the abundance percentage was 20.8%. Dipteran in family Phoridae, Piophilidae, Sepsidae, Drosophildae, and Dolicopodidae were colonized carcasses in a long period of time and were categorized as long term colonizers.